Blurring livelihoods and lives: The social uses of mobile phones and socioeconomic development - Donner, Jonathan (Innovations: Technology, Governance, Globalization, 2009)
This paper focuses on how an intermingling of lives and livelihoods, as mediated by the mobile phone, figures into the micro-processes of economic development. It argues for a perspective on work and on livelihoods that is broad enough to account for (and perhaps even take advantage of) the social processes surrounding these activities. Analysts, policymakers, and technologists interested in the application of Mobiles for Development (M4D) should not ignore the way mobiles blur livelihoods and lives; the developmental and ‘non-developmental’ uses of the mobile are not in competition, nor are they always distinguishable. Instead, the uses of mobiles for developmental and ‘non-developmental’ purposes are often interrelated and sometimes mutually reinforcing. The social functions of the mobile (in matters of connection and self-expression) are helping drive its widespread adoption, and these same functions inform the very behaviors that make the mobile a tool for economic development.